Caracterização do antígeno proteico SsaA de Staphylococcus saprophyticus utilizando estratégias in silico e modelo ex vivo de infecção - Silva, Guilherme Algusto Alves (2020)
Staphylococcus saprophyticus is a Gram-positive bacterium and stands out as the second pathogen responsible for diagnosed cases of urinary tract infection (UTI), affecting mainly young women. Some factors may explain the ability of S. saprophyticus to colonize periurethral, urinary and genital regions, such as the ability to bind to the epithelial tissue of the genitourinary tract and the high activity of the urease enzyme. However, few mechanisms that this bacterium uses to efficiently infect and colonize the host are fully elucidated. In species of the Staphylococcus genus, most of the known virulence factors are proteins or the pathogen's surface. Our research group identified proteins secreted from S. saprophyticus isolates that demonstrated a strong ability to stimulate the immune response in mice and one of the main immunogenic proteins identified was the Staphylococcal Antigen Secreted A (SsaA), not yet characterized in this species. In other species of the Staphylococcus genus, the SsaA protein seems to be related to virulence factors regulated by the same systems, but its specific role during infection has not yet been fully elucidated. In this sense, we propose the characterization of the SsaA protein in S. saprophyticus. Bioinformatics analyzes using the database revealed that the SsaA protein has a CHAP domain with an expected amidase function. The 3D structure of the SsaA protein was predicted through the modeling of proteins using an online server following the validation protocols, the ABCpred server was used to predict epitopes in the SsaA protein. Analysis of the phagocytosis assay revealed that blocking the SsaA protein by sera containing anti-SsaA antibody reduces the number of cells recovered thus indicating that SsaA may be important during the infectious process. Our work will contribute to elucidate the biological function of the SsaA protein, an immunogenic protein that can be useful as a diagnostic target and / or vaccine in this model.